(untitled) (Bombay Hospital Journal, 2026)
Abstract Background: The radial sensory nerve action potential (SNAP) is an important electrodiagnostic study of the upper limbs for a large variety of conditions. Inappropriate distance of stimulation and unavailability of reference data can lead to erroneous conclusions. Objectives: To establish the optimal site of recording the Radial SNAP and obtain reference data for radial SNAP in age-stratified healthy subjects. Materials and Methods: A prospective study was conducted in 181 nerves from healthy subjects aged between 18 years and 86 years, stratified into five groups as per age: a = 18-30 years, b = 31-40 years, c = 41-50 years, d = 51-60 years, e > 61 years. Radial SNAP was recorded antidromically, stimulating at 10 cm from the recording electrode. Mean – 2 standard deviation (SD) of the transformed data was used to generate reference values for amplitudes. Results: The lower limits of amplitude at 10 cm were 28.8, 30.4, 24.4, 23.7 and 16.2 mV for groups a, b, c, d and e, respectively and at 12 cm were 25, 29.2, 18.9, 17.9 and 14.5 mV respectively. A statistically significant difference in amplitudes was noted from the three different sites of stimulation (P < 0.001). A 17% variation in amplitude is explained by age. Height, BMI and wrist girth had minimal effect on the amplitude obtained (r2= 0.05, 0.01, 0.00) Conclusion: This study provides age stratified reference data for antidromic Radial SNAP in Indian population and also gives the optimal site of stimulation of the SNAP.